Effects of fire regime on plant species richness and composition differ among forest, woodland and heath vegetation. Issue 1 (29th November 2017) - Foster, Claire N.; Barton, Philip S.; MacGregor, Christopher I.; Catford, Jane A.; Blanchard, Wade; Lindenmayer, David B.
Abstract: Question: Do the effects of fire regimes on plant species richness and composition differ among floristically similar vegetation types? Location: Booderee National Park, south‐eastern Australia. Methods: We completed floristic surveys of 87 sites in Sydney Coastal dry sclerophyll vegetation, where fire history records have been maintained for over 55 years. We tested for associations between different aspects of the recent fire history and plant species richness and composition, and whether these relationships were consistent among structurally defined forest, woodland and heath vegetation types. Results: The relationship between fire regime variables and plant species richness and composition differed among vegetation types, despite the three vegetation types having similar species pools. Fire frequency was positively related to species richness in woodland, negatively related to species richness in heath, and unrelated to species richness in forest. These different relationships were explained by differences in the associations between fire history and species traits among vegetation types. The negative relationship between fire frequency and species richness in heath vegetation was underpinned by reduced occurrence of resprouting species at high fire frequency sites (more than four fires in 55 years). However, in forest and woodland vegetation, resprouting species were not negatively associated with fire frequency. Conclusions: We hypothesize that differing relationships among vegetation types were underpinned by differences in fire behaviour, and/or biotic and abiotic conditions, leading to differences in plant species mortality and post‐fire recovery among vegetation types. Our findings suggest that even when there is a high proportion of shared species between vegetation types, fires can have very different effects on vegetation communities, depending on the structural vegetation type. Both research and management of fire regimes may therefore benefit from considering vegetation types as separate management units. Abstract : We investigated associations between fire history and plant species richness and composition in three structurally defined vegetation types. Fire frequency was positively associated with species richness in woodland, negatively associated in heath, and unrelated to species richness in forest. These different associations are likely unpinned by variation in fire behaviour, abiotic conditions and biotic interactions among forests, woodlands and heaths.